9.7k views
5 votes
2y - (x + 1)² when x = -4 and y = 9simplify the following

User Evorlor
by
5.1k points

1 Answer

4 votes

We are given the following expression


2y-(x+1)^2

Where the values of x and y are also given as


x=-4\: and\: y=9

It would be much easier if we first substitute the values of x and y then simplify the expression


2(9)-(-4+1)^2

Now let's simplify the expression


\begin{gathered} 2(9)-(-4+1)^2 \\ 18-(-3)^2 \\ 18-(6) \\ 18-6 \\ 12 \end{gathered}

Therefore, the given expression is simplified to 12


\begin{gathered} 2y-(x+1)^2=12 \\ when\: \: x=-4\: and\: y=9 \end{gathered}

User Thamina
by
5.0k points